1988
DOI: 10.3109/00016488809119505
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Features of Vocal Fold Nodules and Polyps

Abstract: Earlier investigation did not show any clear distinctive pathological features that differentiate vocal polyps from vocal nodules. The light microscopic distinctive features between the two lesions point in the direction of a more pronounced epithelial reaction and a more fibrous stromal change in vocal nodules. In the present study, 19 vocal polyps and 11 vocal nodules were subjected to ultrastructural examination aiming at finding distinctive features that may be pathognomic for each of these clinically dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
5

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 0 publications
3
26
0
5
Order By: Relevance
“…Siddapur GK et al [4] also found that vocal nodules are the most common benign vocal fold lesions but with lower incidence rate of 35% observed in their study. Mahesh Chandra et al [5] reported an incidence of 28.57% and 24%, on vocal nodules and vocal polyps respectively. Kotby et al [6] reported similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Siddapur GK et al [4] also found that vocal nodules are the most common benign vocal fold lesions but with lower incidence rate of 35% observed in their study. Mahesh Chandra et al [5] reported an incidence of 28.57% and 24%, on vocal nodules and vocal polyps respectively. Kotby et al [6] reported similar results.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 A literatura aponta uma incidência maior de pólipos em homens do que em mulheres, o que também foi por nós observado neste estudo. 17,25 Vários tipos de alterações morfológicas epiteliais foram observados nas lesões laríngeas inflamatórias neste estudo: hiperplasia, queratose, acantose, paraqueratose, disqueratose e discariose. Não pudemos, porém, diferenciar nódulo, pólipo e cordite edematosa, baseados nestas alterações.…”
Section: Discussionunclassified
“…27 Kotby et al observaram, através de microscopia eletrônica, presença de espessamento epitelial em nódulos e pólipos vocais, sendo mais freqüente nos primeiros. 25 Dikkers, Nikkels estudaram lesões laríngeas inflamatórias, através de microscopia óptica e eletrônica, e observaram hiperqueratose e paraqueratose em intensidade variada. Concluíram que as alterações epiteliais não têm valor, como alteração histológica isolada, para caracterizar uma lesão laríngea inflamatória.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Initial lesion occurs after vocal trauma (sudden movements during phonation), which would take to lesion of blood capillaries, followed by edema, bleeding, thrombosis, formation of fibrin and proliferation of blood capillaries 2 . Some polyps show greater vascularization and less fibrous stroma, whereas others present similar amounts of epithelial and stroma 3 .…”
Section: Introductionmentioning
confidence: 99%